“HIE. Principales factores condicionales en el centro materno periantal de Tarapoto. Periodo 2000” - Pozzi Joseph, Charlotte (2002)
An analytical study was conducted retrospective type cases and controls; in the service of OB/GYN Center maternal Perinatal of Tarapoto, selecting the medical records of all births that occurred from January 1 to December 31 of the year 2000. We studied a total of 180 H. C., of which 90 belonged to the Group of patients with a diagnosis of hypertension induced by pregnancy (HIE) that met the criteria for inclusion and 90 controls without HIE. The information was obtained from the basic Perinatal health record, which provides all the features of the mother (affiliation, background, obstetrical data, etc.); birth (birth canal, gestational age at the time of delivery, etc.) and the newborn (sex, APGAR, etc.). For them calculations statistical is used the program EPI INFO version 6.04, with a range of confidence of the 95% (p < 0.05) calculating the risk relative of each variable in study. In our study, the hypertension Induc...